Analisis Studi Kelayakan Bisnis Usaha Toko Beras Pada Aspek Pemasaran (Studi Kasus Toko Beras Soleh di Pasar Bulak Temu Kabupaten Bekasi ) - Fahri Hidayat; Nur Saran; Dwi Astuti (Jurnal Ekonomi dan Bisnis Digital, 2025)
A business feasibility study is a systematic process to assess whether a business is feasible to run and can be sustainable. This study aims to determine whether the Soleh Rice Shop is feasible to run sustainably. This study uses a qualitative method with a case study research type, in exploring field data the researcher uses data collection techniques in the form of interviews and observations of business owners. The focus of the analysis includes Marketing Strategy, Market Research, Competitor Analysis, Promotion and Branding, and Financial Aspects. The results of this study indicate that the Soleh Rice Shop in Bulak Temu Market is a feasible business to run sustainably. An effective marketing strategy and large market potential make sales stable and even increase. However, there are challenges in facing market competition that will increase over time, the Soleh Rice Shop must prepare a special strategy to maintain customer loyalty.